AGN jet kinetic power and the energy budget of radio galaxy lobes - Godfrey, L.; Shabala, S. (Institute of Physics Publishing, Inc., 2013)
Recent results based on the analysis of radio galaxies and their hot X-ray emitting atmospheres suggest that non-radiating particles dominate the energy budget in the lobes of FR I radio galaxies, in some cases by a factor of more than 1000, while radiating particles dominate the energy budget in FR II radio galaxy lobes. This implies a significant difference in the radiative efficiency of the two morphological classes. To test this hypothesis, we have measured the kinetic energy flux for a sample of 3C FR II radio sources using a new method based on the observed parameters of the jet terminal hotspots, and compared the resulting Q jet-L radio relation to that obtained for FR I radio galaxies based on X-ray cavity measurements. Contrary to expectations, we find approximate agreement between the Q jet-L radio relations determined separately for FR I and FR II radio galaxies. This result is ostensibly difficult to reconcile with the emerging scenario in which the lobes of FR I and FR II radio galaxies have vastly different energy budgets. However, a combination of lower density environment, spectral aging and strong shocks driven by powerful FR II radio galaxies may reduce the radiative efficiency of these objects relative to FR Is and counteract, to some extent, the higher radiative efficiency expected to arise due to the lower fraction of energy in non-radiating particles. An unexpected corollary is that extrapolating the Q jet-L radio relation determined for low power FR I radio galaxies provides a reasonable approximation for high power sources, despite their apparently different lobe compositions.